(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2008)
Arjun (Terminalia arjuna) is a source of many potent, biologically active compounds, planned all over Bangladesh. The chemical examinations of its fruits were taken up to isolate and identify active principles. For this purpose fresh fruits of Terminalia arjuna were extracted with rectified spirit. The extract was then triturated with petroleum ether (40-60°C), which was then subjected to column chromatographic separation followed by PTLC. Such separation led to the isolation of some new pure compounds, TA-1 to TA-5. The structures of compounds were characterized through spectroscopic studies (IR, 1H-NMR and 13C-NMR). Key words: Arjun, TA-1, TA-5, Spectroscopic studies DOI: 10.3329.bjsir.v43i1.863 Bangladesh J. Sci. Ind. Res. 43(1),123-130, 2008